(untitled) (Al-Aasar, 2025)
This study presents an analytical examination of Imam Ahmad Raza Khan’s methodological approach to the reconciliation (tatbīq) of seemingly contradictory narrations in Hadith literature. Imam Ahmad Raza’s scholarly methodology is firmly rooted in the classical traditions of Hadith sciences and Islamic jurisprudence, emphasizing that the statements of the Prophet Muhammad ﷺ do not contain real contradiction; any apparent conflict arises from incomplete understanding. Consequently, his primary principle was to prefer reconciliation and harmonization of narrations, ensuring that no authentic Hadith is discarded without necessity. When reconciliation was not possible, Imam Ahmad Raza employed established principles of tarjīḥ (preference), such as the reliability and precision of narrators, multiplicity of transmission routes, contextual coherence, and conformity with established legal principles. Only as a final resort did he accept abrogation (naskh), considering it an exceptional measure that should not be invoked unless all other possibilities were exhausted. The paper further highlights Imam Ahmad Raza’s exceptional mastery of Usūl al-Hadith, Asmaʾ al-Rijāl, and Jarḥ wa Taʿdīl, demonstrating how his profound knowledge of narrators’ biographies, transmission networks, and critical evaluation enabled him to resolve complex issues of apparent contradiction. A significant case study discussed is his defense and authentication of Imam Muhammad ibn Ishaq, wherein Imam Ahmad Raza systematically refuted allegations against him by presenting extensive testimonies from leading Hadith authorities, thereby establishing Ibn Ishaq’s reliability and scholarly stature. Overall, the research concludes that Imam Ahmad Raza’s contributions to Hadith studies particularly in reconciliation of narrations, critical analysis of transmitters, and principled adherence to classical methodology constitute a lasting scholarly legacy. His work not only preserves the integrity of Prophetic traditions but also provides a rigorous and balanced framework for contemporary Hadith research.